Thermal driven natural convective flows inside the solar chimney flush-mounted with discrete heating sources: Reversal and cooperative flow dynamics. (August 2019) - Ren, Xiu-Hong; Liu, Run-Zhe; Wang, Yun-He; Wang, Lin; Zhao, Fu-Yun
Abstract: Fluid flow and heat transfer mechanism in a solar chimney induced by thermal buoyancy within a range of Ra numbers are reported by numerical and experimental investigations. The transport paths followed respectively by air and heat are visualized by streamlines and heatlines. Numerical results demonstrate that the reverse flow not only slows down the volume flow rate but also accelerates backflow presented in the solar chimney when Ra increases beyond a certain value, which makes the solar chimney lost its role of ventilation. In order to suppress the reverse flow and enhance ventilation performance, a solar chimney with multiple discrete sources flush attached the glazing wall is proposed. The effects of the sizes, positions, and numbers of those discrete heat sources on the system heat transfer rate and volume flow rate are discussed. After comparing with conventional solar chimney, the modified solar chimney with discrete heat source of height D 0  = 1 and position S 0  = 1 could perform better, not only preventing reverse flow but also enhancing the ventilation performance. The results obtained by the lab experimental measurements were agreed well with former numerical simulations. Temperature distributions along the heated wall for different heat input at ambient temperature illustrate the temperatures on the heated wall do not increase linearly and even drop near the top exit. This research could be significant for solar energy utilization and building energy conservation. Highlights: Thermal buoyancy driven natural convection in the solar chimney channel was modeled. Heatlines clearly delineate heat transport structures, similar to streamlines. Heat transfer rates and volume flow rates could be influenced by discrete heat sources. Reverse flow evolves into backflow, at which solar chimney loses the role of ventilation. Solar chimney with discrete heat sources improves ventilation performance significantly.